2022
DOI: 10.3390/polym14102119
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Biopolymer Fabrication in Additive Manufacturing Processing for 3D-Tissue-Engineering Scaffolds

Abstract: The selection of a scaffold-fabrication method becomes challenging due to the variety in manufacturing methods, biomaterials and technical requirements. The design and development of tissue engineering scaffolds depend upon the porosity, which provides interconnected pores, suitable mechanical strength, and the internal scaffold architecture. The technology of the additive manufacturing (AM) method via photo-polymerization 3D printing is reported to have the capability to fabricate high resolution and finely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 122 publications
0
7
0
Order By: Relevance
“…This complex mixture offers adequate biochemical and mechanical support to the surrounding cells, and it controls their performance in the regeneration process [ 9 , 10 ]. However, although TE has been considered a promising strategy to provide biological substitutes that can mimic the ECM, there are still important obstacles to overcome, such as the lack of specific materials for scaffold development and new procedures that enable the processing of delicate polymers such as proteins [ 11 , 12 ]. In this way, hydrogels have been extensively used in these biomedical research fields to overcome the main difficulties, as they can mimic many features of the native cellular microenvironment, due to their suitable properties for this purpose, e.g., their outstanding water retention capacity and flexibility [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This complex mixture offers adequate biochemical and mechanical support to the surrounding cells, and it controls their performance in the regeneration process [ 9 , 10 ]. However, although TE has been considered a promising strategy to provide biological substitutes that can mimic the ECM, there are still important obstacles to overcome, such as the lack of specific materials for scaffold development and new procedures that enable the processing of delicate polymers such as proteins [ 11 , 12 ]. In this way, hydrogels have been extensively used in these biomedical research fields to overcome the main difficulties, as they can mimic many features of the native cellular microenvironment, due to their suitable properties for this purpose, e.g., their outstanding water retention capacity and flexibility [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most studied biopolymers in additive fabrication have been sodium alginate, chitosan, gelatin, and silk fibroin. [ 288 ] Table 4 comprises the literature reports concerning the fabrication of magnetic scaffolds made of natural polymers combined with MNP.…”
Section: Additive Manufacturing In the Fabrication Of Magnetic Materi...mentioning
confidence: 99%
“…Visible light-sensitive photo-initiators are less cytotoxic and more water-soluble than UV light-sensitive photo-initiators, but they cure at a slower rate due to the lower energy level of visible light [ 111 ]. Arifin et al [ 112 ] provided a short review of the effects of various SLA process parameters, such as curing time, power light source/intensity, resolution, layer thickness, and scan velocity on the cured thickness (fill cure depth) of solidified resin, mechanical properties, biocompatibility, and porosity of a biomedical component (i.e., a TE scaffold). It was found that the influence of the process parameters relies not only on the process parameter setup but also on the type and viscosity of the resin, meaning that scaffold properties are defined by the combination of all of these factors.…”
Section: Manufacturing Parameters For Am Of Advanced Biopolymersmentioning
confidence: 99%